Interdisciplinary management of infantile colic (2017)
Infantile colic is one of the main reasons for consultation in pediatric gastroenterology and pediatric nutrition services. This pathology has multiple etiologies such as family dysfunction, gastrointestinal alterations, food allergies or intolerances, food imbalance and improper eating habits. It is acute, of sudden onset, and tends to disappear between 3 and 6 months of age. To date there is no consensus on the management protocols of this condition or indicators of therapeutic efficacy. Medications, dietary regimens and dietary supplements specific to this pathology (anti-colic) have been developed for some years to help address this issue.This article presents a structural review of evidence on the fundamentals and progress in the treatment of infantile colic, and compiles the characteristics of this pathology, the medical and nutritional therapeutic measures, the clinical approach and the techniques to help the patient and his family. This study seeks to provide technical tools to health professionals whose target population is children younger than 2 years of age.